2007
DOI: 10.1111/j.1399-0012.2007.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of health care professionals to brain death: influence on the organ donation process

Abstract: The understanding and acceptance of brain death as a valid determination of death was associated with a positive effect on the level of comfort of health care professionals in performing key donor-related tasks. Reinforcing a positive attitude to brain death among health care professionals may facilitate the procurement process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 17 publications
1
53
0
2
Order By: Relevance
“…19,20 In future situations involving patients, the difficulty of the decision for DBD may thus be assuaged. Several studies on nurses and doctors [21][22][23] have already demonstrated that more information on brain death results in greater acceptance of brain death diagnostics. The questionnaire further reveals that students' motivation to engage with DBD is high both before and after the course ("I am motivated to engage with the topic: evaluation of brain death"), providing evidence that this topic is of fundamental relevance for medical students.…”
Section: Resultsmentioning
confidence: 98%
“…19,20 In future situations involving patients, the difficulty of the decision for DBD may thus be assuaged. Several studies on nurses and doctors [21][22][23] have already demonstrated that more information on brain death results in greater acceptance of brain death diagnostics. The questionnaire further reveals that students' motivation to engage with DBD is high both before and after the course ("I am motivated to engage with the topic: evaluation of brain death"), providing evidence that this topic is of fundamental relevance for medical students.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies agree with these assumptions, having found that most of the studied populations did not accept brain death as death. (4)(5)(6)(7)(8)(9)(10) In Brazil, the diagnosis of brain death in patients with clinical signs of brain death is confirmed by two clinical exams and one complementary test, which are part of care delivery for patient and their families. A major conflict reported by the nurses in our study concerns withdrawing therapeutic support for non-donor patients with a diagnosis of brain death.…”
Section: Discussionmentioning
confidence: 99%
“…(15)(16)(17) In general, research reveals that lack of knowledge about the organ donation process has a negative impact on attitudes toward organ donation, even among health professionals, which can lead to not identifying potential donors and not performing the brain death protocol, identified in practice by actions of professionals involved. (4)(5)(6)8) Nurses perceived religion, lack of communication, and scarcity of human and material resources as situations that could interfere in the process of organs donation.…”
Section: Discussionmentioning
confidence: 99%
“…One proposed topic is to examine the situation of health professionals who are key components of the process, particularly those related to transplantation teams, organ procurement and policy makers. 3 According to some authors, health professionals' knowledge, perceptions and attitudes can become either facilitators or barriers to organ procurement and transplantation 4 and can even influence the public's attitudes toward donation. 5 Nevertheless, few studies have been conducted in Mexico and other Latin American countries on what transplant staff think, say or do regarding the organ donation and transplantation process.…”
Section: Salud Pública De México / Vol 59 No 1 Enero-febrero De 2017mentioning
confidence: 99%